The Christ who embraces: an Orthodox theology of margins - Joseph, Jacob (Theology and mission in world christianity, 2025)
"Jacob Joseph's book, The Christ who Embraces: An Orthodox Theology of Margins, explores the intersection of Orthodox Christian mission and caste dynamics among St. Thomas/Syrian/Orthodox Christians in India. It defines a liturgical touch or embrace in the context of 'untouchability,' where people identify as equal without discrimination, reflecting the inseparable unity of Christ's transcendental (divine) and immanent (human) nature"--